Pollination Biology of Jacaranda oxyphylla with an Emphasis on Staminode Function - Guimaraes, Elza [UNESP]; Di Stasi, Luiz Claudio [UNESP]; Sindronia Maimoni-Rodella, Rita de Cassia [UNESP] (Oxford University Press, 2008)
Background and Aims Bignoniaceae is a Neotropical family with > 100 genera, only two of which, Jacaranda and Digomphia, have a developed staminode. Jacaranda oxyphylla, whose flowers possess a conspicuous glandular staminode, is a zoophilous cerrado species. Here, the composition of the secretion of the glandular trichome and the influence of the staminode on the pollination biology and reproductive success of J. oxyphylla were studied.Methods The floral morphology, pollen viability, stigma receptivity, nectar volume and nectar concentration were studied. Compatibility system experiments were performed and floral visitors were observed and identified. Experiments comparing the effect of staminode presence and absence on pollen removal and pollen deposition efficiency were conducted in open-pollinated flowers. Histochemistry, thin-layer chromatography (TLC) and gas chromatography coupled to flame ionization detection (GC-FID) analyses were performed to determine the main chemical components of the staminode's glandular trichome secretion.Key Results Flower anthesis lasted 2 d and, despite the low frequency of flower visitation, pollination seemed to be effected mainly by medium-sized Eulaema nigrita and Bombus morio bees, by the small bee Exomalopsis fulvofasciata and occasionally by hummingbirds. Small bees belonging to the genera Ceratina, Augochlora and Trigona were frequent visitors, collecting pollen. Jacaranda oxyphylla is predominantly allogamous. Staminode removal resulted in fewer pollen grains deposited on stigmas but did not affect total pollen removal. The secretion of capitate glandular trichome occurs continually; the main chemical compounds detected histochemically were phenolic and terpenoid (essential oils and resins). Monoterpene cineole, pentacyclic triterpenes and steroids were identified by TLC and GC-FID.Conclusions The staminode of J. oxyphyllla is multifunctional and its importance for female reproductive success was attributed mainly to the secretion produced by capitate glandular trichomes. This secretion is involved in complex chemical interactions with pollinating bees, including the solitary bees Euglossini. These bees are common pollinators of various species of Jacaranda.
Keywords: Bignoniaceae; Jacaranda oxyphylla; pollination; bee; staminode; glandular trichomes; reproductive success; terpenes; steroids; phenolics